Precomposting of organic residues and its effect in the population dynamics of Einsenia foetida - Acosta Durán, Carlos Manuel (2013)
Composting and vermicomposting are processes used to transform organic solid residues into fertilizers (compost and vermicompost, respectively). The physical, chemical and biological properties of vermicompost result in improvement of soil fertility and growth of plants. However, both, throughout the process, release toxic substances to the environment. The vermicomposting process tends to result in higher levels of plant availability of most nutrients, as compared with a process of conventional composting. The substrate used to feed the worms must undergo a prior period of precomposting, which involves more time and cost of inputs, which increases the cost of vermicompost obtained, so it is necessary to establish minimum composting time as well as strategies to reduce this period, so that the organic residues can be used as a substrate in the production of the earthworm Eisenia spp. A precomposting process from 0 to 8 weeks, before the vermicomposting process, was evaluated. It was concluded that the conditions under which the experiment took place allowed the development of the worms in all periods of precomposting. Vermicomposting in layers significantly reduces the processing time to achieve complete decomposition of organic residues. For the presence of cocoons and juvenile forms, precomposting is not necessary. Overall, precomposting from 0 to 2 weeks promotes reproduction and precomposting from 3 to 7 weeks promotes individual growth of earthworms. The best treatment was precomposting of 2 weeks, because it facilitates reproduction and average weight gain of the worm. Precomposting is not necessary when vermicomposting piles are less than 50 cm in height, producing vermicompost in 30 days.